Audible acoustic characteristics of epoxy resins with partial discharge - Zhang, Guozhi; Chen, Kang; Zhang, Xiaoxing (Frontiers in Energy Research, 2022)
Epoxy resin is the main solid insulating material for electrical equipment. PD (partial discharge) is an important factor leading to the epoxy resin aging or failure. Fault detection technology based on audible acoustic imaging has the advantages of real-time monitoring, visibility and flexibility, and is gradually being used in the field of electrical equipment insulation state monitoring. However, the audible voiceprint features of epoxy resin with typical PD defects are not clear, which is not conducive to the effective detection and fault diagnosis. Therefore, in this paper, the study of audible voiceprint features of epoxy resin with metal burr, pollution, metal foreign matters and surface discharge defect is carried out. The discharge audible signals are obtained, and its time and frequency domain features are analyzed. The results show that the discharge audible signals of four PD defects can reflect the occurrence of PD simultaneously with pulse current signals. But the characteristics are obviously different in time domain, which are embodied in listening perception, persistence, amplitude and phase. In the frequency domain, the frequency spectrum of discharge audible signals of four defects are mainly composed of components ranging from 5 10 kHz and 13 24 kHz. Further, the three feature vectors of frequency spectrum complexity (H), high-frequency energy factor (Rhf) and maximum frequency point (MaxF) are extracted, which can well distinguish the discharge audible signals of four PD defects.